Assessment of deep inspiration breath hold (DIBH) amplitude and reduction in cardiac dose in left breast cancer patients. Issue 2 (May 2018) - Ledsom, D.; Reilly, A.J.; Probst, H.
Abstract: Introduction: The primary aim of this study was to examine the impact of deep inspiration breath-hold (DIBH) amplitude on subsequent mean heart dose and V30 during radiotherapy. The secondary aim was to investigate if patient age influenced DIBH amplitude. Method: A retrospective study of 30 patients with left-sided breast cancer was completed. Patients were randomly selected from the total number of patients dual scanned in free breathing (FB) and DIBH over a 2-year period. Plans were retrospectively virtually simulated and statistical analysis performed. Results: All patients achieved decreased V30 and mean cardiac dose using DIBH. A positive correlation was found between DIBH amplitude and cardiac V30 dose reduction (p = 0.007, R = 0.48). Ratio of amplitude increase from FB to DIBH and cardiac V30 reduction was positively correlated and statistically significant (p = 0.04, R = 0.38); Ratio of amplitude increase of at least 15 times FB achieved 100% V30 dose reduction, however this was also achieved with ratio increase as low as 6.25 times FB. A statistically significant positive correlation was identified between DIBH amplitude and mean cardiac dose reduction (p = 0.003, R = 0.523). No correlation was found between patient age and amplitude ratio increase (p = 0.602, R = −0.099). Conclusion: A 100% reduction in cardiac V30 can be achieved with a DIBH amplitude increase of 15 times FB. A full reduction can also be achieved at much lower levels (6.25 times FB in current study); however there appears to be no pre-determining patient factors to identify this. DIBH amplitudes of 1 cm–4 cm reduce cardiac mean dose by at least 50%. Highlights: All patients achieved decreased V30 and mean cardiac dose with DIBH. 90% (n = 27) patients achieved at least a 70% reduction in V30 using DIBH. Amplitude increase at least 15 times FB achieves 100% cardiac V30 reduction. 100% V30 reduction achieved with amplitude increase as low as 6.25 times FB. 77% (n = 23) patients achieved relative cardiac mean dose reduction greater than 50%.